One Indigenous Academic’s Evolution: A Personal Narrative of Native Health Research and Competing Ways of Knowing - Stewart, Suzanne L. (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2009)
Indigenous health research should reﬂect the needs and beneﬁts of the participants and their community as well as academic and practitioner interests. The research relationship can be viewed as co-constructed by researchers, participants, and communities, but this nature often goes unrecognized because it is conﬁned by the limits of Western epistemology. Dominant Western knowledge systems assume an objective reality or truth that does not support multiple or subjective realities, especially knowledge in which culture or context is important, such as in Indigenous ways of knowing. Alternatives and critiques of the current academic system of research could come from Native conceptualizations and philosophies, such as Indigenous ways of knowing and Indigenous protocols, which are increasingly becoming more prominent both Native and non-Native societies. This paper contains a narrative account by an Indigenous researcher of her personal experience of the signiﬁcant events of her doctoral research, which examined the narratives of Native Canadian counselors’ understanding of traditional and contemporary mental health and healing. As a result of this narrative, it is understood that research with Indigenous communities requires a different paradigm than has been historically offered by academic researchers. Research methodologies employed in Native contexts must come from Indigenous values and philosophies for a number of important reasons and with consequences that impact both the practice of research itself and the general validity of research results. In conclusion, Indigenous ways of knowing can form a new basis for understanding contemporary health research with Indigenous peoples and contribute to the evolution of Indigenous academics and research methodologies in both Western academic and Native community contexts.